Study on the Tripartite Game Model in Traditional Village Tourism Development: Strategic Evolution and Sustainable Development among Government, Developers, and Residents - Tian, Penghao (International Journal of Social Sciences and Public Administration, 2025)
With the advancement of globalization and urbanization, traditional village tourism development has gradually become an important approach for local economic growth. However, in the process of traditional village tourism development, the interest game among the government, developers, and residents often leads to uneven resource allocation. Therefore, this paper builds a tripartite game model for traditional village tourism development based on evolutionary game theory. It deeply analyzes the game behaviors, interest relationships, and dynamic processes of strategy evolution of the government, developers, and residents under different strategies. First, this paper explains the basic assumptions of the tripartite game in detail. It clarifies the strategy space of the three parties and the method for constructing their payoff matrix. Next, the paper uses the replication dynamics equation to analyze the strategy choices and evolutionary paths of the three parties in different scenarios. It also validates the model’s rationality and effectiveness through numerical simulation. The results show that high-cost investment increases development difficulty, leading all parties to adopt passive strategies. On the other hand, lower costs and higher rewards can promote the active participation of stakeholders and drive the successful implementation of the project. This study provides a theoretical basis for government departments to formulate reasonable policies, mobilize the enthusiasm of all parties. It also offers a theoretical basis for balancing ecological and economic benefits. Additionally, it offers policy recommendations for achieving sustainable development goals